Classical Melodies: An Analysis of the Young People Interest on Classical Guitar in Medan - Ikhsan Putra Wicaksana (Tradition and Modernity of Humanity, 2025)
This study identifies several key factors that contribute to the declination of interest: (1) the limitations of learning materials that are less innovative and adaptive, resulting in saturation and demotivation of learning; (2) the lack of platforms and competition opportunities, which reduces the incentive for students to showcase and develop their capabilities; and (3) the prevalence of other more popular musical instrument choices, such as acoustic and electric guitars, which distract from the unique characteristics of classical guitars. To revitalize the younger generation's interest in classical guitars, innovative strategies in teaching methodologies, the provision of more opportunities for practice and competition, as well as the prominence of the uniqueness and intrinsic excellence of classical guitars are considered essential. This research contributes to a more comprehensive understanding of the dynamics of musical interest in the modern era and provides practical recommendations for the preservation and development of classical guitar art among the younger generation.